Preliminary Validation of the AI Technology Acceptance Instrument for Primary Educators - Zulherman, Zulherman; Rukmana, Diki; Pranata, Khavisa; Supriansyah, Supriansyah; Mansor , Abu Bakar Ahmad Mansor (Yayasan Indonesia Emerging Literacy Education, 2025)
Education in Indonesia has undergone substantial transformation with the widespread integration of technology. In this context, technology training for teachers is essential to enhance the quality of teaching and learning in elementary schools. However, only approximately 30% of teachers report feeling adequately prepared to integrate technology into their instructional practices. This reveals a gap between the increasing demand for educational technology and teachers’ readiness to adopt it. This pilot study aims to evaluate the reliability and construct validity of an adapted instrument designed to measure elementary school teachers’ acceptance of artificial intelligence (AI) technology in East Jakarta, Indonesia. The study incorporates six key constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEU), Social Influence (SI), Facilitating Conditions (FC), Behavioral Intention (BI), and Perceived Trust (PT), with a total of 22 proposed indicators. Data were collected from 61 elementary school teachers who completed a structured questionnaire based on the proposed research model. The results indicate that the instrument meets the required thresholds for both construct validity and reliability. However, only 21 indicators met the established criteria, with one indicator excluded due to low factor loading. The findings from this preliminary study provide a valid foundation for applying the instrument in larger-scale research on teachers’ acceptance of AI technologies in educational settings.